GAMBARAN KUALITAS TIDUR PADA PASIEN GAGAL JANTUNG KRONIK DI RSUD ULIN BANJARMASIN PERIODE OKTOBER-NOVEMBER 2023 - Nasywa, Nabila; Muttaqien, Fauzan; Kaidah, Siti; Darwis, Yulizar; Panghiyangani, Roselina (Universitas Lambung Mangkurat, 2024)
Abstract: Sleep quality is defined as a feeling of satisfaction, freshness, and feeling fit when you wake up, as well as not showing drowsiness or lack of motivation so that it does not interfere with daily activities. Chronic heart failure patients often experienced poor sleep quality. This is related to the symptoms felt by the patient, such as shortness of breath, chest pain and nocturia. In order to describe the quality of sleep among patients with chronic heart failure at Ulin Regional Hospital in Banjarmasin, this study used a cross-sectional, descriptive observational methodology. Purposive sampling was employed in this study in accordance with the inclusion and exclusion criteria for the research. Data was collected by filling in the PSQI questionnaire. The results showed that chronic heart failure patients at Ulin Regional Hospital, Banjarmasin had poor sleep quality (77.32%). The majority of respondents were aged 51-60 years (45.33%). If we look at gender characteristics, there are 62.6% of men and 37.3% of women who have poor sleep quality. Based on the symptoms frequently felt by respondents, 53.33% complained of shortness of breath, 36% of chest pain and 10.66% of nocturia Keywords: sleep quality,chronic heart failure, PSQI questionnare Abstrak: Kualitas tidur diartikan sebagai rasa puas, segar, dan merasa bugar saat bangun tidur, serta tidak menunjukkan rasa kantuk atau kurang motivasi sehingga tidak mengganggu aktivitas sehari-hari. Kualitas tidur yang buruk sering dialami pasien gagal jantung kronik. Hal tersebut berkaitan dengan gejala-gejala yang dirasakan pasien, seperti sesak napas, nyeri dada, dan nokturia. Kualitas tidur pasien gagal jantung kronik di RSUD Ulin Banjarmasin diteliti dengan menggunakan desain observasional deskriptif cross-sectional. Teknik pengambilan sampel menggunakan teknik purposive sampling yang sesuai dengan persyaratan inklusi dan eksklusi penelitian. Pengambilan data diambil dengan pengisian kuesioner PSQI. Hasil penelitian menunjukkan bahwa pasien gagal jantung kronik di RSUD Ulin Banjarmasin memiliki kualitas tidur buruk (77,32%). Mayoritas responden berumur 51-60 tahun (45,33%). Jika dilihat dari karakteristik jenis kelamin, terdapat 62,6% laki-laki dan 37,3% perempuan yang mempunyai kualitas tidur buruk. Berdasarkan gejala yang sering dirasakan responden, 53,33% mengeluhkan sesak napas, 36% nyeri dada, dan 10,66% nokturia. Kata-kata kunci: kualitas tidur, gagal jantung kronik, kuesioner PSQI